Do business linkages play a role in upgrading workers’ skills among small and medium-sized enterprises in Vietnam? - Dao Thi Thu Giang; Cao Thi Hong Vinh (Journal of International Economics and Management, 2022)
Business linkages are of interests to many firms as they can have positive impacts on firms’ performance. Nevertheless, there have been few studies on possible influence of business linkages on motivation to upgrade workers’ skills among small- and medium-sized enterprises (SMEs). Applying a Probit estimation model with Fixed-Effects techniques for panel data with a sample covering more than 6,000 observations of SMEs from Vietnam, the study provides key findings. First of all, the increase in the number of business linkages helps SMEs to upgrade workers’ skills by reducing the percentage of unskilled workers. Secondly, the rise in workers’ skills increases the probability that SMEs train their existing workers, but not new workers. Finally, the increase in firm size plays an important role for SMEs in Vietnam to upgrade their workers’ skills.